Pembuatan Media Promosi Berbasis Web, Sistem Administrasi, dan Manajemen Pemasaran pada Mitra Kelompok Usaha Bersama (KUB) Nelayan di Kelurahan Pulau Temoyong, Batam - Andi Maslan; Erlin Elisa; Raymond Raymond (Universitas Mathla'ul Anwar Banten, 2019)
MAKING WEB-BASED PROMOTION MEDIA, ADMINISTRATION SYSTEM, AND MARKETING MANAGEMENT IN JOINT BUSINESS GROUP OF FISHERMANS IN PULAU TEMOYONG VILLAGE, BATAM. Batam City is a municipality which has a strategic location directly adjacent to Singapore which is included in the Riau Islands Province. The current reality is that the contribution of the fisheries sector to the regional treasury of Batam is relatively small and is still dominated by other sectors. Some obstacles faced are the lack of knowledge in the field of Information Technology (ICT), especially how to promote aquaculture and catches that are less than the maximum, resulting in a decrease in sales turnover for fishermen. This is felt by the Fishermen Joint Business Group (KUB). This KUB is spread in six villages in the Bulang Sub-District, Batam. Each village is approximately 20 KUB consisting of 10 members. This KUB certainly regulates production and coordinates with regard to the development of fisheries and capture aquaculture products. In the process of cultivation and capture there are no problems, resulting in decreased sales turnover, decreased sales turnover ranging from 10% to 20%, according to interviews with the service team, that one of the consequences is due to the lack of ICT-based promotional media (E-commerce Website), lack of computer-based administrative system management and lack of knowledge in the field of marketing. To avoid ongoing problems, web design training with MDA models and participant satisfaction analysis have been carried out involving 30 participants who are members of a fishing business group. The overall result in the implementation of the training to the community was that 79.58% of participants were satisfied with the training, and there were some inputs that the material provided was too difficult and the training time was also limited.